1995
DOI: 10.1111/j.1365-2761.1995.tb00300.x
|View full text |Cite
|
Sign up to set email alerts
|

Virulence of Flavobacterium branchiophilum in experimentally infected salmonids

Abstract: The ability of selected strains of Flavobacterium branchiophilum to attach to and colonize the gills of five species of teleosts (four salmonid and one cyprinid) and cause mortality was investigated. In virulence studies with F. branchiophilum strain LAB4a, cumulative mortality was dose-dependent in rainbow trout, Oncorhynchus mykiss (Walbaum), and ranged from 0 to 75%. However, regardless of dose, the relative amount of gill-associated F. branchiophilum antigen inereased lh after challenge. The gill-associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…Indeed, the gill pathology observed in this study is also similar to what is reported in fish suffering from bacterial gill disease, caused by F. branchiophilum (Wakabayashi, Huh & Kimura 1989). For example, pale and swollen gills due to a proliferative hyperplasia of the gill epithelium that results in fusion of neighbouring lamellae is hallmark of infections associated with F. branchiophilum (Bullock 1990;Ostland et al 1995).…”
supporting
confidence: 85%
See 1 more Smart Citation
“…Indeed, the gill pathology observed in this study is also similar to what is reported in fish suffering from bacterial gill disease, caused by F. branchiophilum (Wakabayashi, Huh & Kimura 1989). For example, pale and swollen gills due to a proliferative hyperplasia of the gill epithelium that results in fusion of neighbouring lamellae is hallmark of infections associated with F. branchiophilum (Bullock 1990;Ostland et al 1995).…”
supporting
confidence: 85%
“…For example, pale and swollen gills due to a proliferative hyperplasia of the gill epithelium that results in fusion of neighbouring lamellae is hallmark of infections associated with F. branchiophilum (Bullock ; Ostland et al . ).…”
Section: Bacterial Challenge Dose and Total Mortality In Chinook Salmmentioning
confidence: 97%
“…Bacterial diseases of freshwater fish epithelia have been extensively studied with the primary focus upon bacteria from the Cytophagales, such as bacterial gill disease caused by Flavobacterium branchiophilum (Ostland et al 1994(Ostland et al , 1995, and necrotizing skin diseases such as columnaris disease caused by F. columnare (Thomas-Jinu & Goodwin 2004) and bacterial cold-water disease caused by F. psychrophilum (Cipriano et al 1996 and review by Nematollahi et al 2003). However, in marine fishes relatively few bacterial skin and gill diseases have been characterised.…”
Section: Introductionmentioning
confidence: 99%
“…Gill tissues were thawed and processed and 96well plates were coated with soluble gill antigen, as described by Ostland et al (1995). The GAFBA was estimated with an elisa, as previously described (MacPhee, .…”
Section: Bacterial Clearancementioning
confidence: 99%